Profiling of Somatic Mutations in Phaeochromocytoma and Paraganglioma by Targeted Next Generation Sequencing Analysis - Andrea Luchetti; Diana Walsh; Fay Rodger; Graeme Clark; Tom Martin; Richard Irving; Mario Sanna; Masahiro Yao; Mercedes Robledo; Hartmut P. H. Neumann; Emma R. Woodward; Farida Latif; et al. (International Journal of Endocrinology, 2015)
At least 12 genes (FH, HIF2A, MAX, NF1, RET, SDHA, SDHB, SDHC, SDHD, SDHAF2, TMEM127, and VHL) have been implicated in inherited predisposition to phaeochromocytoma (PCC), paraganglioma (PGL), or head and neck paraganglioma (HNPGL) and a germline mutation may be detected in more than 30% of cases. Knowledge of somatic mutations contributing to PCC/PGL/HNPGL pathogenesis has received less attention though mutations in HRAS, HIF2A, NF1, RET, and VHL have been reported. To further elucidate the role of somatic mutation in PCC/PGL/HNPGL tumourigenesis, we employed a next generation sequencing strategy to analyse “mutation hotspots” in 50 human cancer genes. Mutations were identified for HRAS (c.37G>C; p.G13R and c.182A>G; p.Q61R) in 7.1% (6/85); for BRAF (c.1799T>A; p.V600E) in 1.2% (1/85) of tumours; and for TP53 (c.1010G>A; p.R337H) in 2.35% (2/85) of cases. Twenty-one tumours harboured mutations in inherited PCC/PGL/HNPGL genes and no HRAS, BRAF, or TP53 mutations occurred in this group. Combining our data with previous reports of HRAS mutations in PCC/PGL we find that the mean frequency of HRAS/BRAF mutations in sporadic PCC/PGL is 8.9% (24/269) and in PCC/PGL with an inherited gene mutation 0% (0/148) suggesting that HRAS/BRAF mutations and inherited PCC/PGL genes mutations might be mutually exclusive. We report the first evidence for BRAF mutations in the pathogenesis of PCC/PGL/HNPGL.